Spontaneous decay of small carbon cluster dianions Cn2− (n=7-11). Issue 23 (January 2020) - Najeeb, P K; Stockett, M H; Anderson, E K; Eklund, G; Kristiansson, M K; Rosén, S; Chartkunchand, K C; Gnaser, H; Golser, R; Hanstorp, D; Cederquist, H; Schmidt, H T; et al.
Synopsis: We have studied the stabilities of small carbon dianion clusters, C n 2 − (n = 7 – 11) in the cryogenic electrostatic ion storage ring, DESIREE. We observe spontaneous electron emission for tens of milliseconds, where dianions containing an even number of carbons decay slower in comparison to their neighbouring cluster sizes. For all the systems considered here, we find that there is a component which is stable at least on the time scales of hundreds of milliseconds.